Das quantifizierte EEG im elektroenzephalogrammbasierten Monitoring während Allgemeinanästhesie - Kaiser, H. A. (Anaesthesist, 2021)
The electroencephalogram (EEG) is increasingly being used in the clinical routine of anesthesia in German-speaking countries. In over 90% of patients the frontal EEG changes somewhat predictably in response to administration of the normally used anesthetic agents (propofol and volatile gasses). An adequate depth of anesthesia and appropriate concentrations of anesthetics in the brain generate mostly frontal oscillations between 8 and 12 Hz as well as slow delta waves between 0.5 and 4 Hz. The frontal EEG channel is well-suited for avoidance of insufficient depth of anesthesia and excessive administration of anesthetics. This article explains the clinical interpretation of the most important EEG patterns and the biophysical background. Also discussed are important limitations and pitfalls for the clinical routine, which the anesthetist should know in order to utilize the EEG as an admittedly incomplete but clinically extremely important parameter for the level of consciousness.